U-Th whole rock data and high spatial resolution U-Th disequilibrium and U-Pb zircon ages of Mt. Erciyes and Mt. Hasan quaternary stratovolcanic complexes (Central Anatolia) - Friedrichs, Bjarne; Schmitt, Axel Karl; McGee, Lucy; Turner, Simon (Data in Brief, 2020)
Thirty-eight lava and pyroclastic samples were collected from Mt. Erciyes and Mt. Hasan, the two largest stratovolcanic complexes of the Central Anatolian Volcanic Province in Turkey. More than 1000 zircon crystals were dated by Secondary Ion Mass Spectrometry (SIMS) applying U-Th disequilibrium and U-Pb methods. Model ages were calculated from zircon 230Th-238U-232Th isotopic compositions in combination with U-Th whole rock data of digested lava samples generated by Multi-Collector Inductively Coupled Plasma Mass Spectrometry (MC-ICP-MS). Middle and Late Pleistocene ages dominate the dataset, but are complemented by both older (predominantly Early Pleistocene) and younger (Holocene) ages. U-Th disequilibrium and U-Pb zircon data provide maximum eruption ages that can be further specified by (U-Th)/He geochronology (zircon double dating). Additionally, these data are important to constrain the longevity and size of magmatic systems, and their potential for reactivation leading to potentially hazardous eruptions.